Distribution and degree of heterogeneity of the afimbrial-adhesin-encoding operon (afa) among uropathogenic Escherichia coli isolates. - Labigne-Roussel, A (1988)
The afimbrial adhesin (AFA-I) from a pyelonephritic Escherichia coli isolate (KS52) is a mannose-resistant, P-independent, X-binding adhesin, expressed by the afa-1 operon. It is distinct from the E. coli X-binding adhesins with M and S specificity. A total of 138 E. coli isolates belonging to various serotypes, mostly from urinary tract infections, were screened for the presence of DNA sequences related to the afa operon and for the expression of an X-adhesin able to mediate mannose-resistant hemagglutination (MRHA) and adhesion to uroepithelial cells. Fifteen strains were shown to harbor DNA sequences related to the AFA-I-encoding operon, and 13 of them expressed an X-adhesin. Using as probes different DNA segments of the AFA-I-encoding operon in Southern experiments, we demonstrated that only three of these clinical isolates contained genetic determinants closely related to those identified in the original afa prototype strain (KS52): presence of the afaA, afaB, afaC, afaD, and afaE genes associated with the expression of a 16,000-dalton hemagglutinin-adhesin which strongly cross-reacted with AFA-I-specific antibodies. The other E. coli isolates harbored DNA sequences homologous to the afaA, afaB, afaC, and afaD genes, but lacked the sequence corresponding to the adhesin-producing gene afaE; Western blots allowed the detection of polypeptides (15,000, 15,500, or 16,000 daltons) in these strains which cross-reacted with variable intensity with antibodies raised against the denatured AFA-I protein, but did not cross-react with native AFA-I-specific antibodies. Following DNA cloning experiments from chromosomal DNA of two of those strains (A22 and A30), we demonstrated that although the AFA-related operon in A22 and A30 strains lacked the AFA-I adhesin-encoding gene, they synthesized a functional X-adhesin. Thus, strains A22 and A30 encode adhesins designated AFA-II and AFA-III, which were cloned on recombinant plasmids pILL72 and pILL61, respectively. Southern hybridization experiments and Western blot analyses of the 15 AFA-related strains demonstrate the heterogeneity of the genetic sequences encoding the structural adhesin and suggest the bases for the serological diversity of the AFA adhesins.